Consumer Involvement for Durable and Non Durable Products:Key Indicators and their Impact - Solanki, Sapna (Indian Journal of Marketing, 2011)
Involvement refers to how much time, attention, energy and other resources people devote for purchasing or learning about the product or one of the fundamental concepts used to explain the consumer buying process. Study finds that how level of consumer involvement for durable and non durable products are influenced by financial risk, performance risk, physical risk, social risk, time risk, uncertainty in selection, psychological risk, previous shopping experiences, product attributes, situation, brand personality, hedonic value, motivation, level of learning, utility of the product, price, durability, gift (for whom a product is purchased), life style, store, frequency of use, additional benefits/offers, packaging and endorsement. A self design opinionnaire was framed to find out the various dimensions influencing on consumer involvement. For dependent variable (consumer involvement), Zaichkowsky's (1985) unidimensional - a 20 items bipolar likert scale called Personal-Involvement-Inventory (PII) was adapted. The study was conducted during January 2009 to May 2009. Stepwise regression was used for both durable and non durable product categories. The regression method suggested four models for each product. The best model suggests that level of consumer involvement while purchasing garments is influenced by Previous Shopping Experiences, Hedonic Value, Special Offer and Uncertainty. The Laptop model explains that Brand Personality, Hedonic Value, Frequency of Use and Durability are the core predictors.